HUBUNGAN ANTARA KETERPAJANAN ASAP ROKOK DENGAN KEJADIAN TUBERKULOSIS PADA ANAK DI RSUD DR. SOEKARDJO KOTA TASIKMALAYA - Etty Komariah Sambas; Enok Nurliawati (LPPM Universitas Bakti Tunas Husada, 2015)
Tuberculosis in Indonesia is still a health problem which requires specific strategy to overcome. Morbidity rate is increasing in 2009 as 228 cases per 100.000 population to 235 cases per 100.000 population. TB prevalence in Indonesia is 0.4 percent in which West Java is the provence with highest TB prevalence as 0.7 percent (Riskesdas, 2013). TB could be suffered by adult and children. TB in children can inhibit growth and development and can lead to complications that can lead to death. This study aimed to determine correlation between cigarette smoke exposure and TB in children. Research was conducted at Dr. Soekardjo Hospital Tasikmalaya in March-April 2015. The study design was descriptive correlational using case control approach. Sampling technique was consecutive sampling with accidental sampling method. The sample size for the cases group was 47 respondents and control group was 47 respondents. Data collection used questionnaires. Data analysis was univariate and bivariate Chi Square (X ²) with significance level of 5% (α= 0.05) or 95% Confidence Interval. Results showed a significant correlation between cigarette smoke exposure and TB in children (p value = 0.023 ). OR = 2.613 (CI: 0.867 - 7.608), meaning that children who were exposed to cigarette smoke have an opportunity to 2,613 times suffered from TB compared to children who were not exposed to cigarette smoke suffering from TB.